Regression Study on the Impact of Vehicular Emission Pollutants on Ozone Level: Chemical and Material Perspectives - Ekwumemgbo, Patricia Adamma; Okon, Idongesit Edem (Bumi Publikasi Nusantara, 2023)
This study verified the impact of vehicular emission pollutants and meteorological factors on the variability of ground-level ozone in Port Harcourt, Nigeria using multiple linear regression (MLR) analysis (p=0.05). Data were collected at traffic hot spots over twelve calendar months (December 2017 and November 2018). The explanatory variables were precursor pollutants (NO2, CO, and VOCs) and meteorological factors (temperature, relative humidity, and wind speed). Data collected were subjected to correlation analyses, and O3 concentrations showed a significant positive correlation with NO2, CO, VOCs, and traffic density (p= 0.05). O3 levels also correlated positively with temperature and negatively with wind speed and relative humidity across traffic periods. Three Models: Model 1, Model 2, and Model 3 were generated from MLR analyses for the estimation of O3 variation in the morning peak traffic period, off-peak traffic period, and evening peak traffic period respectively. Validation of performance for each Model was achieved using performance statistics including adjusted R2, mean absolute error (MAE), mean biased error (MBE), mean square error (MSE), and root mean square error (RMSE).